Prospects on the Use of Schizochytrium sp. to Develop Oral Vaccines - Ramos-Vega, Abel; Rosales-Mendoza, Sergio; Bañuelos-Hernández, Bernardo; Angulo, Carlos (Frontiers in Microbiology, 2018)
Although oral subunit vaccines are highly relevant in the fight against widespread diseases, their high cost, safety and proper immunogenicity are attributes that have yet to be addressed in many cases and thus these limitations should be considered in the development of new oral vaccines. Prominent examples of new platforms proposed to address these limitations are plant cells and microalgae. Schizochytrium sp. constitutes an attractive expression host for vaccine production because of its high biosynthetic capacity, fast growth in low cost culture media, and the availability of processes for industrial scale production. In addition, whole Schizochytrium sp. cells may serve as delivery vectors; especially for oral vaccines since Schizochytrium sp. is safe for oral consumption, produces immunomodulatory compounds, and may provide bioencapsulation to the antigen, thus increasing its bioavailability. Remarkably, Schizochytrium sp. was recently used for the production of a highly immunoprotective influenza vaccine. Moreover, an efficient method for transient expression of antigens based on viral vectors and Schizochytrium sp. as host has been recently developed. In this review, the potential of Schizochytrium sp. in vaccinology is placed in perspective, with emphasis on its use as an attractive oral vaccination vehicle.